Polyamines as salinity biochemical marker in callus of Eucalyptus urograndis. - Lima, Giuseppina Pace Pereira; Piza, Isabela M. Toledo; Henrique, Andréa; Takaki, Massanori (Ciência Florestal, 2005)
Biochemical markers have been used for the analysis of plant cells submitted to several types of stress, among them salinity. This work aimed at analyzing the effect of saline stress in callus of Eucalyptus urograndis on polyamine contents. Explants (hypocotyls) obtained from seeds were inoculated in callus inductive medium, submitted to different levels of NaCl and analyzed at 10, 20 and 30 days after the inoculation. The free polyamines were extracted, isolated and quantified using TLC (Thin-Layer Chromatography). Putrescine content was higher and a fall in the spermidine content was observed in callus submitted to salinity condition. The results showed that polyamine accumulation is related to NaCl exposure in callus of Eucalyptus urograndis. The decrease in spermine content could be used as a biochemical marker for Eucalyptus callus subjected to salinity.